Strengthening Religious Moderation at the Nurul Islam Antirogo Jember Islamic Boarding School - Mohamad Faqih; Zainal Abidin; Khoirul Faizin (Cita konsultindo, 2023)
The erosion of national attitudes and religious tolerance as well as excessive religious fanaticism within the firqah (class) often results in horizontal conflicts between fellow human beings. Such a phenomenon of mainstream thinking has made the Nurul Islam Islamic boarding school take an important role in strengthening religious moderation in preventing the entry of various kinds of religious thoughts that are contrary to the culture of Indonesian society. This study aimed to understand and reveal the strengthening of perspectives, attitudes and practices of nationalism and tolerance at the Nurul Islam Islamic boarding school. This research used a qualitative approach in the form of field research. Data analysis was presented in a qualitative descriptive manner as obtained from informants. The results of this study indicated that the strengthening of religious moderation in the Nurul Islam Islamic boarding school is through several aspects, including: a) strengthening nationalism through early education and formal education. While the forum for strengthening implementation is through: book recitation, seminars, training, discussions, bahtsul masail, deepening the understanding of aswajaan and socialization. b) Strengthening national attitudes, namely through: extracurricular activities and PHBN activities. c) Strengthening national practices, namely through: the example of the kiai, through the discipline of Islamic boarding schools, religious students, mutual cooperation, helping each other and being fair. Strengthening in the aspect of tolerance, namely in the form of: a) strengthening the perspective of tolerance, namely through: yellow book studies, formal education, seminars, literacy, ukhuwah character training, aswajaan studies and cooperation between outside agencies. Strengthening understanding for teachers, namely such as: training, debriefing on the aqeedah of aswaja and teacher's morning call. b) Strengthening tolerance, such as: religious activities for students, activities (PHBI), cultural enterpreneur bazaars and art performances (PENSI). c) Strengthening the practice of tolerance, including the application of a balanced attitude, respecting differences, the application of noble character, solidarity and hospitality practices.